OHSAS Certification and learning with work accidents in the construction sector - Silva, S.A.; Oliveira, M.J.; Carvalho, H.; Jacinto, C.; Soares, C. (14th European Congress of Work and Organizational Psychology: Developing people in 21st century organizations: local and global perspectives, 2009)
Safety and Health certifications constitute a key tool to help companies to improve the quality of work conditions and prevent occupational fatalities and diseases. Specifically, OHSAS 18001 (Occupational Health Safety Management Systems – Specification) offer an integrative management system that is internationally recognized to enable organizations to manage their occupational health and safety risks, and thus improve their overall performance. In addition, it has been acknowledged the need to use accident information for prevention through learning (e.g., Koornneef, 2000; Toft & Reynolds, 1997). Until now, as far as it is our knowledge, research has not explored the link between OSHAS certification and companies practices for learning with incidents and accidents. In this paper we will present four case studies conducted in the construction sector that aimed to characterize organisational practices for collecting and analysing accidents information in order to improve safety learning and accidents prevention. All the companies have OHSAS certification and we will explore their similarities and differences in their learning practices. This study is part of a research project (CAPTAR – Learn to prevent) that has as one goal of establishing strategies and processes to learn efficiently with accidents and that will cover all the cycle phases. The data was collected using long semi-structured interviews with key organisational stakeholders. The interview protocol covered information, such as: type of accident records; existence of a formal procedure for accident investigation; what accident forms are used; procedures used in the data collection; procedures used in accident analysis, and finally, how these organisations use the relevant information towards safety learning and improvement. Overall interviews length and documentation collection varies between two and five hours. In addition to the interview, relevant organisational documentation was also being collected and analysed in this study. Results will focus Company’s learning practices comparing between them and also comparing to OHSAS practices recommendations. At the moment data is still being analysed but preliminary results reveal that all companies analyse and discuss accidents information, recognize their own failures and analyse risks. Nevertheless we found differences in procedures and activities in information treatment, in responsibilities and also in the internal accidents information dissemination. In our paper we will discuss OHSAS opportunities for learning and prevention of accidents and implications for research and intervention will be addressed.